Transition Metal Layered Double Hydroxide Nanosheets for Breast Cancer Drug Delivery - Irfandi, Rizal (Hayyan Journal, 2025)
This review synthesizes research on transition metal layered double hydroxide nanosheets in breast cancerdrug encapsulation to address challenges in targeted delivery, drug resistance, and controlled release. Thereview aimed to evaluate synthesis and functionalization strategies, benchmark drug loading and releaseprofiles, elucidate metal doping effects on targeting and uptake, compare therapeutic outcomes, and identifyclinical translation barriers. Literature selection focused on experimental in vitro and in vivo studies publishedup to mid-2024, emphasizing physicochemical characterization, cellular internalization, and therapeuticefficacy. Findings reveal that transition metal doping and surface modifications enable ultrahigh drug loadingcapacities with pH-responsive, tumor-specific release, enhancing intracellular delivery via receptor-mediatedand endocytic pathways. Multifunctional nanosheets demonstrate synergistic anticancer effects throughcombined chemo-, photothermal, and immunotherapies, with favorable biocompatibility and low systemictoxicity in preclinical models. However, variability in synthesis reproducibility, incomplete mechanisticunderstanding of metal ion interactions, and limited long-term safety data impede clinical translation.Integrating these findings underscores the potential of transition metal-doped LDH nanosheets as versatileplatforms for breast cancer nanotherapy while highlighting the need for standardized evaluation andcomprehensive in vivo assessments. These insights inform future research directions toward optimizingnanosheet design and advancing clinical applications in precision oncology.